Comprehensive database of land subsidence in 143 major coastal cities around the world: overview of issues, causes, and future challenges - Pedretti, Laura; Giarola, Alessia; Korff, Mandy; Lambert, John; Meisina, Claudia (Frontiers in Earth Science, 2024)
Subsidence, the gradual lowering or the sudden sinking of the ground surface, is known to cause impact in terms of damage to infrastructures, utility lines, buildings and changes in surficial drainage system and groundwater conditions. Additionally, the impacts of land subsidence will be greater in the future considering the sea level rise, the population growth, the intensification of coastal erosion and extreme events, the increase of flood risk or freshwater salinization, mostly in coastal cities. The main aim of this work is to provide an open-source, peer-reviewed and comprehensive database that identifies the main and secondary causes of land subsidence in 143 coastal cities. It highlighted how in some at-risk cities the potential impact of subsidence is still unknown and no mitigation measures exist. The database additionally showed that mitigation measures, specifically those addressing subsidence due to groundwater extraction, have proven successful in the past. The database (Pedretti et al., 2023; https://doi.org/10.5281/zenodo.8349293) aims to increase the knowledge of the phenomenon and to rise the global awareness of land subsidence issues among the researchers, the scientific community, the stakeholders and the policymakers also in terms of urban planning and development.